ACTIVITIES EXTENSION OF PHYSICAL EDUCATION IN UERJ FLAG A BIAS APPROACH TO EXTERNAL COMMUNITY WITH BRAZILIAN PUBLIC UNIVERSITY. (Fiep Bulletin - online, 2011)
This paper aims to provide a diagnosis of outreach in the Course of Physical Education at the State University of Rio de Janeiro (UERJ), which has been deeply involved in the process of consolidation of university extension and academic practice. Using numerous programs, projects and activities, the Institute of Physical Education and Sports has fueled the University to interact with the external community. To better understanding and comprehension of the potential extension becomes necessary mechanisms to evaluate it and organize it from the results and impacts. As Coordinator of LAMGRES - Multidisciplinary Laboratory of Rhythmic Gymnastics with a focus on Education and Health IEFD / UERJ, we have encouraged the practice of extension activities, mainly through its interaction between the internal and external communities. One such activity is a subproject "Talks with workshop. Receiving professionals from various related disciplines and with the collaboration of members of social impact projects, this activity has gained trust and confidence of the outside community. Among the many objectives of this activity are the ones that more clearly, explain the academic and social commitment of the University. Should pay special attention to the opportunities they offer to graduates for reflection and action around issues of Physical Education in constant tune with the real needs and interests of the communities in which they are contextualized. Thus, it is important that the activities that establish as clearly as possible the limits of field experience, to enable participants to clearly identify the objectives of the activity, encouraging results achieved.
Keywords: Education; Continuing education; Rhythmic Gymnastics